Spin Dictators : The Changing Face of Tyranny in the 21st Century - Guriev, S. M.; Treisman, Daniel (Book collections on Project MUSE., 2022)
Spin Dictators traces how leaders such as Singapore's Lee Kuan Yew and Peru's Alberto Fujimori pioneered less violent, more covert, and more effective methods of monopolizing power. The book reveals why most of today's authoritarians are spin dictators-and how they differ from the remaining "fear dictators" such as Kim Jong-un and Bashar al-Assad, as well as from masters of high-tech repression like Xi Jinping.